Desenvolvimento de modelo de previsão de falência bancária: sua aplicabilidade no sector bancário de Moçambique - Intupo, Reis Castigo (2021)
In Mozambique, no study has been identified related to bankruptcy forecasting modelsdeveloped in theireconomic context,and the existing models were developed internationally and in a very different economic context from their own, so that they do not fit their reality.Meanwhile, related to the bankruptcy, the national banking sector was one of the ones that wereshaken in the last decade, resulting onthe intervention of the Bank of Mozambique to two banks(Moza Banco, S.A and Nosso Banco, S.A)due to deteriorationof their financial and prudential indicators. So,as it seemsimportant and imminentthe academic action infindingways to improve methods of predicting bankruptcy risk, minimizing bankruptcy situations in the credit sector, through techniques inserted in Mozambiqueeconomic context,the objective of the present research is to propose a bankruptcy risk prediction model for the national banking sector, developed through innovations of methods already disseminated internationally.For this purpose, 4commercial bankswere identified(Moza Banco, S.A, Nosso Banco, S.A,Barclays Bank Moçambique, S.AandBanco Terra, S.A),which served as a sample for the development of the model. These were divided into 2 groups: group 1 consisting of 2 intervened banks, considered in the present research as bankrupt banks. Group 2 consists of the banks considered hitherto as healthy(the last two mentionedabove). On sequence, three financial ratios belonging to the category of capital structure ratios, asset return and asset concentration were identified, which are considered in the literature as good predictors of bankruptcy risk in the banking sector. From these assumptionsthe model was developed and the 3 classification zones were determined, namely the zone with high risk of bankruptcy, zone of uncertainty and the zone of lower risk of bankruptcy. Subsequently, for thepurpose of testing the model, a further 6 commercial bankswere identified(Banco Único, SA, FNB Moçambique, SA, African Banking Cooperation (Moçambique), SA, Ecobank Moçambique, SA, Capital Bank (Mozambique), SA and Société Générale Moçambique, SA). The model presented a level of precision of 75%, meaning a good bank risk prediction capability, so it is recommended that it be used by bank managers and others stakeholders.